Impact of inland pollution sources on the bacteriological water quality of the Southern Ganghwado Bay Area, South Korea. Issue 1 (2nd January 2017) - Kang, Chang-Ho; Oh, Soo Ji; Shin, YuJin; Kim, YongGyeong; Oh, Eun-Gyoung; So, Jae-Seong
Abstract : The bacteriological pollution of water is a serious global environmental issue. The pollution of water by human and animal wastes can be a source of hazardous pathogens, which may pose serious health risks. In this study, we evaluated the microbiological water quality in the southern Ganghwado Bay area, South Korea. A total of 30 samples (14 discharge water samples from the drainage area and 16 sea water samples from the adjacent area) were analyzed for the concentrations of total coliforms (TC) and fecal coliforms (FC) in November 2013. The highest concentration of FC (28, 000 MPN/100 mL) was found at site L1 (inland). The highest mean concentrations of coliforms were found at sites W9 (sea water) and W11 (sea water), with TC and FC concentrations of 33 MPN/100 mL. In conclusion, site L1 located near W9 and W11 is clearly identified as the main source of pollution at Dongmak Beach.